CORPORATE STRATEGIES OF INTERNATIONAL COMPANIES: AN EXPERIENCE OF ANALYSIS OF FOREIGN RESEARCHES - M. A. Lyashenko (Модернизация, инновация, развитие, 2015)
In article, based on a wide theoretical material of foreign researches, the author gives the review of a current state of degree of a readiness of a question of corporate strategies of the international companies.